Climatic variability on groundwater recharge of Mymensingh district in Bangladesh - Akhter, S; Sharmin, A; Islam, MT; Ullah, MS (Progressive Agriculture, 2019)
A study was carried out in Mymensingh sadar upazila of Bangladesh in order to evaluate the effects of climatic variability on groundwater (GW) recharge and evapotranspiration (ET) over the period of 2006 - 2015. The annual GW recharge was computed by using soil moisture balance method, while CROPWAT-8.0 model was used to determine potential evapotranspiration (PET) and Grindley method was also used to estimate actual evapotranspiration (AET). In the case study area, the average temperature and rainfall showed no trend (almost constant), whereas humidity showed a declining trend over the study period. Analysis of rainfall trend revealed that there was considerable increase in annual rainfall with a mean of 2125 mm found over the study period. Groundwater recharge showed an increasing trend over the whole period, and the maximum recharge of 247.86 mm found in 2013, while maximum GW depletion of 136.8 mm found in 2014. In case of annual PET, the maximum of 1403.76 mm found in 2006, whereas the minimum of 1115.76 mm found in 2013. The AET showed a slightly declining trend over the 10 years of study, and the highest average AET of 1014.24 mm observed in 2007, whereas the lowest of 772.92 mm was in 2013. There was no significant relationship among groundwater recharge and annual variability of average temperature, and average rainfall found while only the annual variability of average humidity was found to be inversely related with groundwater recharge. Progressive Agriculture 30 (1): 104-112, 2019